Effects of in-sewer dosing of iron-rich drinking water sludge on wastewater collection and treatment systems. (15th March 2020) - Rebosura, Mario; Salehin, Sirajus; Pikaar, Ilje; Kulandaivelu, Jagadeeshkumar; Jiang, Guangming; Keller, Jürg; Sharma, Keshab; Yuan, Zhiguo
Abstract: The use of coagulants and flocculants in the water and wastewater industry is predicted to increase further in the coming years. Alum is the most widely used coagulant, however, the use of ferric chloride (FeCl3 ) is gaining popularity. Drinking water production that uses FeCl3 as coagulant produces waste sludge rich in iron. We hypothesised that the iron-rich drinking water sludge (DWS) can potentially be used in the urban wastewater system to reduce dissolved sulfide in sewer systems, aid phosphate removal in wastewater treatment and reduce hydrogen sulfide in the anaerobic digester biogas. This hypothesis was investigated using two laboratory-scale urban wastewater systems, one as an experimental system and the other as a control, each comprising sewer reactors, a sequencing batch reactor (SBR) for wastewater treatment, sludge thickeners and anaerobic digestion reactors. Both were fed with domestic wastewater. The experimental system received in-sewer DWS-dosing at 10 mgFe L −1 while the control had none. The sulfide concentration in the experimental sewer effluent decreased by 3.5 ± 0.2 mgS L −1 as compared with the control, while the phosphate concentration decreased by 3.6 ± 0.3 mgP L −1 after biological wastewater treatment in the experimental SBR. The dissolved sulfide concentration in the experimental anaerobic digester also decreased by 15.9 ± 0.9 mgS L −1 following the DWS-dosing to the sewer reactors. The DWS-doing also enhanced the settleability of the mixed liquor suspended sludge (MLSS) (SVI decreased from 193.2 ± 22.2 to 108.0 ± 7.7 ml g −1 ), and the dewaterability of the anaerobically digested sludge (the cake solids concentration increased from 15.7 ± 0.3% to 19.1 ± 1.8%). The introduction of DWS into the experimental system significantly increased the COD and TSS concentrations in the wastewater, and consequently the MLSS concentration in the SBR, however, this did not affect normal operation. The results demonstrated that iron-rich waste sludge from drinking water production can be used in the urban wastewater system achieving multiple benefits. Therefore, an integrated approach to urban water and wastewater management should be considered to maximise the benefits of iron use in the system. Graphical abstract: Image 1 Highlights: Fe-rich DWS dosed to sewers effectively decreases dissolved sulfides in sewers. Fe-rich DWS dosed to sewers aids in P removal during wastewater treatment. Fe-rich DWS dosed to sewers decreases sulfides in the AD sludge. Fe-rich DWS dosed to sewers improves settleability and dewaterability of sludge. Fe-rich DWS-dosing elevates MLSS in the WWTP.